Identification of triterpene from the leaves and bark of kopsia singapurensis Ridl. (SELADA) (IR) - Lee, Yean Shan (2015)
This study was aimed to extract and identify chemical compounds isolated from the leaves and barks of Kopsia singapurensis. The isolated compounds were evaluated for cytotoxic (MCF-7), antibacterial (Bacillus cereus) and antioxidant activity (DPPH). The isolation process was carried out using chromatographic techniques such as column chromatography and thin layer chromatography. The structures of isolated compounds were elucidated through spectroscopic analysis including 1D-NMR (1H, 13C and DEPT), 2D-NMR (1H-1H COSY, HSQC/HMQC and HMBC), IR, UV, MS (GCMS); also by comparison with previous literature data. Isolation study on the leaves of K. singapurensis has yielded lupeol 147, mixture of stigmasterol 148 and - sitosterol 149, lupeol ester 150, and a mixture of lupeol 147, -amyrin 151 and - amyrin 152. Compounds -amyrin 152, -amyrenone 153, -amyrin acetate 154 and lupeol acetate 155 were successfully isolated from the bark of K. singapurensis. These triterpenoids were isolated for the first time from this species. Compounds 147, 150, 152, 153, 154 and 155 were exhibited cytotoxic effects against MCF-7 in the range of IC50 15.5 - 26.0 g/mL. All isolated compounds showed weak antioxidant activity (IC50 >500 g/mL) and were not active against Bacillus cereus. Kopsia singapurensis was one of the threatened species however there is no publication on terpene isolated from this species. Hence, study on the chemical constituents of K. singapurensis has been embarked to discover new active compound for pharmaceutical industries.